Teaching Portuguese abroad: my experience at the University of the West Indies, Jamaica - Christina dos Reis , Patricia (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
This article describes my experience teaching Portuguese as a Foreign Language at the University of the West Indies in Jamaica. It presents a description of students, their objectives and the opportunities of cultural enrichment that they had while Portuguese students at the university. The article also includes brief descriptions of works that contributed to my reflections as a language instructor abroad: the role of motivation in acquisition of knowledge, learning beyond the school walls and the use of different learning strategies. The article still makes reference to Brazilian program PEC-G and Portuguese proficiency exam Celpe-Bras.